Calcio come inclusione sociale. Studio di caso: l’A.S.D. Napoli Calcio Femminile e Maschile - Luca Bifulco; Rosalba Sarnataro (Culture e Studi del Sociale)
The article analyzes the case of A.S.D. Napoli Calcio Femminile e Maschile, a non-profit association from Naples, which aims to use sport as a factor of social inclusion. The social utility of sport lies in its ability to promote personal – psychological and relational well-being – and broader social and economic benefits. However, sport can also be the site of social exclusion, since not all social groups have the same opportunities. The research tries to understand how the interventions of the sport association analyzed are able to be inclu-sive for boys and girls, especially those belonging to lower classes, considering that the ef-fectiveness of the measures is influenced by the contexts in which it works.